The Impact of University-Industry-Cooperative Partnerships on Entrepreneurship Training for Youth in Marginalised Communities - Elizabeth Oluwakemi Ayandibu (Indonesian Journal of Community Engagement, 2025)
This paper examines the impact of university–industry–cooperative partnerships on knowledge transfer, innovation, and skills development within higher education. Drawing on a comprehensive literature review, the study highlights the growing importance of collaborative engagement between academic institutions, industries, and cooperatives in addressing contemporary socio-economic challenges. The review reveals that such partnerships enhance the relevance of academic programmes by aligning them with industry needs, thereby equipping graduates with practical skills that improve employability and entrepreneurial readiness. They also facilitate innovation through joint research projects, knowledge co-creation, and the commercialization of academic outputs, thereby contributing to economic development. Furthermore, the study underscores the role of cooperatives as important stakeholders in these partnerships, particularly in contexts where community development and inclusive economic growth are priorities. By engaging cooperatives, universities not only strengthen local development initiatives but also encourage socially responsive research and teaching practices. Despite these benefits, the literature identifies persistent challenges such as misaligned objectives, resource constraints, and weak policy support, which can limit the effectiveness of such collaborations. Overall, the review demonstrates that sustainable university–industry–cooperative partnerships require strong governance structures, mutual trust, and supportive policy environments. The paper concludes that strengthening these collaborations is critical for improving innovation ecosystems, promoting inclusive growth, and ensuring that higher education contributes meaningfully to both economic and social development.